2008
DOI: 10.1056/nejmoa0707302
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone for Low Libido in Postmenopausal Women Not Taking Estrogen

Abstract: In postmenopausal women not receiving estrogen therapy, treatment with a patch delivering 300 microg of testosterone per day resulted in a modest but meaningful improvement in sexual function. The long-term effects of testosterone, including effects on the breast, remain uncertain. (ClinicalTrials.gov number, NCT00131495.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
266
3
16

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 414 publications
(294 citation statements)
references
References 39 publications
9
266
3
16
Order By: Relevance
“…Without estrogen/progesterone replacement therapy Davis et al 140 Natural/surgical T Transdermal (patch) 150/300 mg per day 52 weeksAbbreviations: CRP, C-reactive protein; HDL-C, high-density lipoprotein-cholesterol; MT, methyltestosterone, T, testosterone; TU, testosterone undecanoate; m, positive association; k, negative association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without estrogen/progesterone replacement therapy Davis et al 140 Natural/surgical T Transdermal (patch) 150/300 mg per day 52 weeksAbbreviations: CRP, C-reactive protein; HDL-C, high-density lipoprotein-cholesterol; MT, methyltestosterone, T, testosterone; TU, testosterone undecanoate; m, positive association; k, negative association.…”
Section: Discussionmentioning
confidence: 99%
“…Studies monitoring the effects of testosterone therapy only provide a better model for studying these effects. Only recently, the effect of testosterone only was investigated in a 52-week double-blind placebo-controlled trial 140 in which postmenopausal women received a patch delivering 150 or 300 mg of testosterone per day or placebo. In this study, circulating levels of TT, FT and BT showed a dose-related increase with testosterone treatment, but no difference in lipid profile and glucose metabolism was observed between women treated with testosterone compared with placebo.…”
Section: Postmenopausal Testosterone Therapymentioning
confidence: 99%
“…The current recommendation for testosterone treatment is that therapy should be restricted to short-term therapy until long-term safety issues have been resolved. The number of adverse events associated with testosterone replacement treatment in women has been limited when protocols of treatment are optimized to achieve physiologic levels of circulating testosterone (67).…”
Section: Supplementation Of Testosterone and Dhea-s In Womenmentioning
confidence: 99%
“…Hormones affect the brain by binding to specific receptors, and previous work suggests that differences in the organization of brain areas in males and females depend on hormones (14-16). Hormones may affect cognition, mood, well-being, sexuality, and social behavior (16)(17)(18)(19).However, the existing evidence on the relationship between sex hormones and economic behavior is merely correlative. It does not admit causal inference.…”
mentioning
confidence: 99%